2007
DOI: 10.1038/sj.jid.5700875
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-Cultural Inequivalence of Dermatology-Specific Health-Related Quality of Life Instruments in Psoriasis Patients

Abstract: The dermatology life questionnaire index (DLQI) and the Skindex are the most commonly used dermatology-specific health-related quality of life (HRQOL) instruments. Although these tools are used in international surveys and clinical trials, the cross-cultural equivalence of their items has not been documented. We used differential item functioning (DIF), which is part of the Rasch model, to assess the impact of cultural background on the items of the DLQI and Skindex-29 and-17. The data of the 450 psoriasis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 29 publications
4
82
1
3
Order By: Relevance
“…Although a comparative study of different categorization techniques in the same sample would have been very interesting, we were unable to do this due to the lack of a patient-based anchor in this study. In addition, validation studies are required to test the generalizability of the findings of this study in patient samples that differ in diagnosis, disease severity and cultural background because these factors may affect HRQOL assessment [2, 4, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Although a comparative study of different categorization techniques in the same sample would have been very interesting, we were unable to do this due to the lack of a patient-based anchor in this study. In addition, validation studies are required to test the generalizability of the findings of this study in patient samples that differ in diagnosis, disease severity and cultural background because these factors may affect HRQOL assessment [2, 4, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Nijsten et al [26] discussed the problem of cross-cultural inequivalence of dermatology-specific QoL instruments. Even in the case of equal total QoL scores in patients from different countries, the difference between separate QoL item scores may be significant [27].…”
Section: The Problem Of Cross-cultural Inequivalence Of Hrqol Instrummentioning
confidence: 99%
“…The DLQI is a reliable and valid instrument [7,10,11] . However, it has fallen short in some other aspects of psychometric performance in particular unidimensionality and item bias [12][13][14][15] . Hongbo et al [16] have demonstrated a banding system to aid the interpretation of DLQI scores, but a frequent question still arises: what does a specific improvement, such as 2, 5 or 6 points, in a DLQI score mean to a patient (and to the physician)?…”
Section: Introductionmentioning
confidence: 99%